Pengembangan Aplikasi Perangkat Bergerak Pembelajaran Pengenalan Buah-Buahan dalam Bahasa Inggris Menggunakan Speech Recognition (Studi Kasus : RA Al-Mawaddah) - Rahma Nur Anggraeni; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Learning English for early childhood begins with an introduction to the environment. One of them is fruit material. Based on the observations of researchers in the RA Al-Mawaddah case study, teaching English in early childhood teachers was limited to providing material about listening and speaking. In this study explained the development of Android-based English learning applications by utilizing Android Speech recognition. Android Speech Recognition is a library provided by Android to identify sounds by digitizing words and matching the digital signals with a pattern stored in the database. The use of Android Speech Recognition for the development of English learning media will facilitate the process of learning activities by both teachers and students. Based on the results of testing validation, and usability, it was found that the functional requirements expected from the application were valid. Based on the results of usability testing the results obtained 81.56%, ie the application is valid which means the system is easy to learn, efficient, easy to remember, errors easily overcome, and satisfy the user. For the accuracy test results produce a score of 100% where the appraisal is in accordance with or the same as the assessment by the teacher.